PRODUCTION OF OLIGOFRUCTOSE SYRUP BY ENZYMATIC HYDROLYSIS FROM INULIN-CONTAINING CHICORY SYRUP - T. S. Puchkova; D. M. Pikhalo; O. M. Karasyova (Пищевые системы, 2020)
The purpose of the work is to study the enzymatic hydrolysis of inulin-containing syrups of various purification degrees from chicory chips in the production of oligofructose to be used in dietary, diabetic and health-preventive nutrition products. It has been determined that ion exchange purification of the syrup is necessary for hydrolysis. Individual stages of ion-exchange purification are specified using a two-stage scheme: К1-А1-К2-А2 and an additional stage on the “Macronet” sorbent MN200 to stabilize pH and remove bitterness taste. Requirements for the quality of syrup for hydrolysis have been developed: pH value — 4.5–5.0; chromaticity — not more than 0.5 units opt. den.; ash — not more than 0.2%; protein — 0.5%; no bitterness taste. Optimal conditions for hydrolysis of inulin-containing syrup have been established using Novozim 960 endoinulinase (Denmark): temperature — 55–58 °C; pH — 4.7–5.2; DS (dry substance) — 19%; preparation dosage — 0.4 units. INU/g of syrup DS; time 20–24 h. A sample of oligofructose syrup was obtained using the preparation “Novozim 960.” The carbohydrate composition of oligofructose after the inulin hydrolysis was determined: fructooligosaccharides (FOS) — 70.12%; oligofructosides — 24.79%; disaccharides — 2.11%; fructose — 2.98%. Requirements for carbohydrate composition of oligofructose obtained by enzymatic hydrolysis of inulin-containing syrup have been developed: sum total of FOS and oligosaccharides — not less than 93%, sum total of di- and monosaccharides — not more than 7%.